2012
DOI: 10.1136/tobaccocontrol-2012-050470
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and adult perceptions of traditional and novel smokeless tobacco products and packaging in rural Ohio

Abstract: Objective As smokeless tobacco (ST) marketing increases and new products emerge on the market, very little is known about consumer perceptions of ST products. To inform development of future ST counter-marketing approaches, this qualitative study examined consumer perceptions of traditional and novel ST products and packaging. Methods Focus groups and qualitative interviews were held with adolescent (n=23; mean age of 17 years) and adult (n=38; mean age of 29 years) male ST users from rural Ohio counties. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…A survey of young adults in Minnesota reported that 64.8% of participants were aware of snus, 14.5% used snus in their lifetime, and 3.2% used snus in the past 30 days (Choi & Forster, 2012). Studies on attitudes towards snus were mainly qualitative focus groups investigations (Wackowski, Lewis, & Delnevo, 2011; Bahreinifar, Sheon, & Ling, 2013; Choi, Fabian, Mottey, Corbett, & Forster 2012; Liu et al, 2012). Across all four of these studies, participants expressed positive attitudes towards snus because it is convenient and can be used anywhere, including in smoke-free environments and in schools.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of young adults in Minnesota reported that 64.8% of participants were aware of snus, 14.5% used snus in their lifetime, and 3.2% used snus in the past 30 days (Choi & Forster, 2012). Studies on attitudes towards snus were mainly qualitative focus groups investigations (Wackowski, Lewis, & Delnevo, 2011; Bahreinifar, Sheon, & Ling, 2013; Choi, Fabian, Mottey, Corbett, & Forster 2012; Liu et al, 2012). Across all four of these studies, participants expressed positive attitudes towards snus because it is convenient and can be used anywhere, including in smoke-free environments and in schools.…”
mentioning
confidence: 99%
“…Across all four of these studies, participants expressed positive attitudes towards snus because it is convenient and can be used anywhere, including in smoke-free environments and in schools. The discreet nature of snus was perceived to lead to reduced stigma, because snus users would not be subject to stigma associated with traditional snuff or chew (Liu et al, 2012) or with second-hand smoke (Wackowski et al, 2011). Participants noted the different flavors of snus as its appealing characteristic, which could potentially entice youth (Liu et al, 2012) or encourage recreational use of snus (Choi et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the cluster -U.S. taste market‖, cigarettes again became an object of study. Liu et al (2014) analyzed consumers' perception of traditional and new products and concluded that cigarette packaging significantly affects consumer perception and behavior. Thus, standard information on cigarette packaging, such as shape, size, and images, must be a part of comprehensive tobacco control.…”
Section: Figure 5 Network Between Countriesmentioning
confidence: 99%
“…10 A study of snus sales in Minnesota indicated that an underage buyer was successful in 12.9% of his or her purchase attempts, suggesting that the percent of purchases of snus appears to be higher/easier than the successful purchase attempts of cigarettes. 11 An internet study of YouTube videos of smokeless tobacco indicated that there were no restrictions on youth creating or viewing the videos and that only 9.8% had public health messages and only 12.2% presented the effects of nicotine in the videos.…”
Section: Introductionmentioning
confidence: 99%